A gestão do design como diferencial de qualidade nas indústrias moveleiras do Alto Uruguai gaúcho - Silva, José Paulo Medeiros da (2011)
The development of technological innovation, driven by the internationalization process of companies, products and markets, is triggering major changes in economic performance, competition, in deregulation and in the revolution of knowledge. In this sense, the construction of new solutions for products and services and, mainly, the reconciling of the industrial products to their demands, become essential to the enterprises restructuring, in order to integrate the characteristics of an open and demanding market. Realizing of essential importance to understand what function and role design plays in the national furniture industry and to understand how its products are developed, the focus of this study is to identify culturally how the furniture industry in Alto Uruguai/RS operates, and how Design Management can generate competitive advantage, add value to the product and help to increase sales. To perform the study, it was necessary to provide an overview of the furniture industry of Alto Uruguai/RS, emphasizing the application of design in the development of new products. The report was supported by bibliographic and documental resources, structured and semi-structured interviews and also by fieldwork. The research showed that the vast majority of companies demonstrate to understand the importance of design for the development of its products; however, there are few that invest in its accomplishment. This conservative attitude in the point of view of some managers is, in part, related to the paradigm which is associated to short-term view, in which design is seen only as a cost. Therefore, the design management, being a means of integration and interaction of different areas, can reverse this situation by promoting in the companies the competitive differential that is so necessary for their survival, such as the economic development in the region in which it operates.